PENGARUH UKURAN PERUSAHAAN, UMUR PUBLIKASI, MASA PERIKATAN AUDIT, PERGANTIAN MANAJEMEN PADA KUALITAS AUDIT - Paramita, Ni Ketut Ayu; Latrini, Ni Made Yenni (E-Jurnal Akuntansi, 2015)
Improving the quality of audits required to increase investor confidence in the company's financial statements. Competent and independent is one of the conditions produce a quality audit. Discretionary accruals are used as a measure of audit quality. The aim of the study to determine the effect of firm size, age of the publication, period of the audit engagement, and management changes on audit quality. Quality audits on companies listed in Indonesia Stock Exchange (IDX) 2011-2013 is the object of other research. Determination of the samples was done by purposive sampling technique, in order to get 78 companies manufacturing. Hypothesis testing using multiple regression analysis technique, which is preceded by the classical assumption. Based on the analysis found that the size and age of the publication has no effect on audit quality. The period of the audit engagement and management turnover negative effect on audit quality.
Keywords: audit quality, firm size, firm age, period of the audit engagement, management turnover